Controlling the Diameters of Nanotubes Self‐Assembled from Designed Peptide Bolaphiles. Issue 12 (12th February 2018) - Zhao, Yurong; Yang, Wei; Wang, Dong; Wang, Jiqian; Li, Zongyi; Hu, Xuzhi; King, Stephen; Rogers, Sarah; Lu, Jian R.; Xu, Hai
Abstract: Controlling the diameters of nanotubes represents a major challenge in nanostructures self‐assembled from templating molecules. Here, two series of bolaform hexapeptides are designed, with Set I consisting of Ac‐KI4 K‐NH2, Ac‐KI3 NleK‐NH2, Ac‐KI3 LK‐NH2 and Ac‐KI3 TleK‐NH2, and Set II consisting of Ac‐KI3 VK‐NH2, Ac‐KI2 V2 K‐NH2, Ac‐KIV3 K‐NH2 and Ac‐KV4 K‐NH2 . In Set I, substitution for Ile in the C‐terminal alters its side‐chain branching, but the hydrophobicity is retained. In Set II, the substitution of Val for Ile leads to the decrease of hydrophobicity, but the side‐chain β‐branching is retained. The peptide bolaphiles tend to form long nanotubes, with the tube shell being composed of a peptide monolayer. Variation in core side‐chain branching and hydrophobicity causes a steady shift of peptide nanotube diameters from more than one hundred to several nanometers, thereby achieving a reliable control over the underlying molecular self‐assembling processes. Given the structural and functional roles of peptide tubes with varying dimensions in nature and in technological applications, this study exemplifies the predictive templating of nanostructures from short peptide self‐assembly. Abstract : Dimension control: The designed short peptide bolaphiles tend to form nanotubes. By varying the core side‐chain branching and hydrophobicity of the hydrophobic amino acids, the nanotube diameter can be well tuned from more than one hundred to several nanometers, with the tube shell always being composed of a constant peptide monolayer.